2022
DOI: 10.1155/2022/9140461
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Copper Homeostasis-Related Gene FOXO1 as a Novel Indicator for the Prognosis and Immune Response of Breast Cancer

Abstract: Copper (Cu) is one of the essential microelements for all living systems. Studies have illustrated the biological significance of Cu homeostasis in human cancers, including breast cancer (BRCA). Nevertheless, the detailed roles of Cu homeostasis in BRCA need to be further explored. Here, we identified a downregulated Cu homeostasis-related gene FOXO1 and investigated the potential functions of FOXO1 in BRCA through several bioinformation databases. The BRCA patients with high level of FOXO1 displayed favorable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, Voli and colleagues stated a strong correlation between PD-L1 expression and intracellular copper levels, noting that copper dysregulators inhibit PD-L1 in vitro and in vivo , resulting in increased tumor-infiltrating lymphocytes ( Voli et al, 2018 ). In a recent study, Zeng demonstrated that FOXO1, a gene significantly associated with PDCD1, downregulated copper homeostasis is a novel indicator of breast cancer prognosis and immune response ( Zeng et al, 2022 ). The TIDE database related analysis confirmed the above points of our view.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Voli and colleagues stated a strong correlation between PD-L1 expression and intracellular copper levels, noting that copper dysregulators inhibit PD-L1 in vitro and in vivo , resulting in increased tumor-infiltrating lymphocytes ( Voli et al, 2018 ). In a recent study, Zeng demonstrated that FOXO1, a gene significantly associated with PDCD1, downregulated copper homeostasis is a novel indicator of breast cancer prognosis and immune response ( Zeng et al, 2022 ). The TIDE database related analysis confirmed the above points of our view.…”
Section: Discussionmentioning
confidence: 99%
“… 44 A study of Zeng et al reported that FOXO1 was associated with immune cell infiltration, immune checkpoint expression, and response to immunotherapy in breast cancer. 45 It has been found that FOXO1 expression was also responsible for stemness and sensitivity of breast cancer cells to chemotherapeutic agents, such as tamoxifen and paclitaxel. 46 , 47 Combined with our results, it can be inferred that hsa_circ_0007823 overexpression may inhibit the progression of TNBC through regulating the miR-182-5p/FOXO1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells relying on glycolysis are around 1000 times more sensitive to copper ion inducers than cells depending on mitochondrial respiration. Conversely, ferredoxin 1 (FDX1) lowers CU2+ to CU+, encouraging lipoylation and aggregation of enzymes responsible for controlling the mitochondrial TCA cycle (63). On the other hand, FDX1 results in the instability of iron-sulfur proteins (Fe-S), which sets off a stress response in the mitochondria and produces cuproptosis (64).…”
Section: Mechanism Of Cuproptosismentioning
confidence: 99%